Reduced probability of smoking cessation in men with increasing number of job losses and partnership breakdowns. Issue 6 (30th August 2010) - Kriegbaum, M; Larsen, A M; Christensen, U; Lund, R; Osler, M
Abstract : Background: Unemployment and partnership breakdowns are common stressful life events, but their association with smoking cessation has been investigated in only a few studies. Objective: To investigate how history of employment and cohabitation affects the probability of smoking cessation and to study joint exposure to both. Methods: Birth cohort study of smoking cessation of 6232 Danish men born in 1953 with a follow-up at age 51 (response rate 66.2%). History of unemployment and cohabitation was measured annually using register data. Information on smoking cessation was obtained by a questionnaire. Results: The probability of smoking cessation decreased with the number of job losses (ranging from 1 OR 0.54 (95% CI 0.46 to 0.64) to 3+ OR 0.41 (95% CI 0.30 to 0.55)) and of broken partnerships (ranging from 1 OR 0.74 (95% CI 0.63 to 0.85) to 3+ OR 0.50 (95% CI 0.39 to 0.63)). Furthermore, smoking cessation was associated with the duration of the periods of unemployment (ranging from 1–5 years (OR 0.75, 95% CI 0.65 to 0.85) to 10–23 years (OR 0.29, 95% CI 0.22 to 0.38)) and with living without a partner for >5 years (ranging from 6–9 years to 10–23 years (OR 0.80, 95% CI 0.66 to 0.97) to 10–23 years (OR 0.44, 95% CI 0.37 to 0.52)). Those who never cohabited and experienced one or more job losses had a particular low chance of smoking cessation (OR 0.19, 95% CI 0.12 to 0.30). Conclusion: The numbers of job losses and of broken partnerships were both inversely associated with probability of smoking cessation.